Risperidone-Associated Neuroleptic Malignant Syndrome in an Inpatient With Schizophrenia, With Successful Rechallenge and 3 Year Follow-Up - Chen, Ting-Ren; Chen, Ying-Chang (Frontiers in Psychiatry, 2018)
Neuroleptic malignant syndrome (NMS) is rare but one of the most serious adverse effects of antipsychotics. Here, we report a case of risperidone-associated NMS in which a successful rechallenge of risperidone was observed with a positive follow-up. A 47-year-old female with schizophrenia was treated with risperidone 4 mg/d for 8 months in 2009 and was admitted to our hospital in 2015 owing to violent behavior under persecutory delusions. Risperidone 2 mg/d was initiated and increased to 4 mg/d 54 days later. Further, long-acting injectable (LAI) risperidone 25 mg per two weeks was added on hospital day 15. On hospital day 116, NMS occurred and thus we discontinued all antipsychotics including LAI risperidone, then NMS improved. We resumed LAI risperidone 25 mg per two weeks on hospital day 148, thus we waited for 22 days before re-starting the drug treatment. She was discharged on hospital day 371, then switched to LAI paliperidone 150 mg per four weeks 2 months later. At the time of a follow-up 3 years later, NMS had not reoccurred. This case reports on an unusual presentation of NMS in which no hyperthermia was observed. Furthermore, this case indicated that NMS may occur in a dose-dependent manner. In conclusion, this case reported important information for clinicians with regard to antipsychotic drug rechallenges and proper dosing of APs to avoid or reverse NMS.